Electrochemical and spectroscopic characterisation of organic molecules with high positive redox potentials for energy storage in aqueous flow cells - Cannon,CG; Klusener,PAA; Brandon,NP; Kucernak,ARJ (Energy Advances, 2024)
We show that a number of ubiquitous organic molecules used as redox mediators and chemically sensing species can be used as positive couples in electrochemical energy storage. Air and acid stable organic molecules were tested in aqueous acid electrolytes and employed as the positive electrolyte in H2–organic electrochemical cells. The dissolved organic species were characterised in-operando using UV-vis spectroscopy. N,N,N′,N′-tetramethylbenzidine was found to be a stable and reversible redox organic molecule, with a 2 e− molecule−1 capacity and a 0.83 V cell potential. N-Oxyl species were also tested in purely aqueous acidic flow battery electrolytes. A H2–violuric acid cell produced a reversible potential of 1.16 V and demonstrated promising redox flow cell cycling performance.